Luminance measurement for curved surface sources with an imaging luminance measurement device. (4th November 2015) - Yu, Hsueh-Ling; Young, Richard; Hsiao, Chin-Chai
Abstract: Due to the advantages of fast measurement speed, imaging luminance measurement devices (ILMDs) have become more and more popular in the recent years. However, even though an ILMD is corrected by flat field calibration, the measured results deviate from the real values when measuring curved surface sources. The deviation is larger in particular when the curvature of the source is smaller or when the source is unlike a Lambertian source. This paper shows how to obtain correction factors to increase the measurement accuracy of the ILMD when measuring different types of curved surface sources. The issue of how the measurement conditions affect the level of image blur is also discussed in this paper.